Follicular lymphoma patients with a high FLIPI score and a high tumor burden: A risk stratification model - Andjelić, Boško; Todorović-Balint, Milena; Antić, Darko; Bila, Jelena; Djurašinović, Vladislava; Mihaljević, Biljana (Vojnosanitetski pregled, 2013)
Background/Aim. The widely accepted Follicular Lymphoma International Prognostic Index (FLIPI) divides patients into three risk groups based on the score of adverse prognostic factors. The estimated 5-year survival in patients with a high FLIPI score is around 50%. The aim of this study was to analyse the prognostic value of clinical and laboratory parameters that are not included in the FLIPI and the New Prognostic Index for Follicular Lymphoma developed by the International Follicular Lymphoma Prognostic Factor Project (FLIPI2) indices, in follicular lymphoma (FL) patients with a high FLIPI score and high tumor burden. Methods. The retrospective analysis included 57 newly diagnosed patients with FL, a high FLIPI score and a high tumor burden. All the patients were diagnosed and treated between April 2000 and June 2007 at the Clinic for Hematology, Clinical Center of Serbia, Belgrade. Results. The patients with a histological grade > 1, erythrocyte sedimentation rate (ESR) ≥ 45 mm/h and hypoalbuminemia had a significantly worse overall survival (p = 0.015; p = 0.001; p = 0.008, respectively), while there was a tendency toward worse overall survival in the patients with an Eastern Cooperative Oncology Group (ECOG) > 1 (p = 0.075). Multivariate Cox regression analysis identified a histological grade > 1, ESR ≥ 45 mm/h and hypoalbuminemia as independent risk factors for a poor outcome. Based on a cumulative score of unfavourable prognostic factors, patients who had 0 or 1 unfavourable factors had a significantly better 5-year overall survival compared to patients with 2 or 3 risk factors (75% vs 24.1%, p = 0.000). Conclusion. The obtained results suggest that from the examined prognostic parameters histological grade > 1, ESR ≥ 45 mm/h and hypoalbuminemia can contribute in defining patients who need more aggressive initial treatment approach, if two or three of these parameters are present on presentation
Keywords: lymphoma; follicular; antineoplastic combined chemotherapy protocols; prognosis